Statuts épistémologique et axiologique de la « théorie » architecturale. Pour une définition normative de la théorie en architecture - Adrien Marchand (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
Architectural theory lies in a rather peculiar and ambigous status among various practical fields. On the one hand, its writing in time and by various authors seems to indicate the construction of a shared and objective knowledge, analogous to the theories formulated in the field of science. On the other hand, its normative part endorse an oriented axiological character, in the extend that it aims to formulate values. If its impact in architectural field is undoubted, architectural theory’s study of is still complicated, if not avoided by the tenets of doctrinals approaches. Instead of proposing a study of one particular architectural theory, we aim to clarify the architectural theory’s status and the various ways it could take on the epistemological and axiological grounds — i.e. regarding the knowledge and values it produces.